Çarpışma tamponu tasarımı - Kurt, Umut (Fen Bilimleri Enstitüsü, 2020)
Geçmişten bugüne demiryolu araçları ulaşım konusunda önemli bir yere sahiptir. Bu hususta, demiryolu güvenliği de önem kazanmaktadır. Özellikle, demiryolu araçlarının güvenli bir taşıma aracı olması için vagonlar ve diğer mekanik aksamlar standartlarda belirtilen nitelikleri sağlamak zorundadır. Standartlarda belirtilen bu nitelikler, tasarımı yapılan unsura yine aynı standartlarda belirtilen statik ve dinamik test uygulamaları ile ölçülmektedir. Demiryolu araçlarında pek çok mekanik aksam bulunmaktadır. Bu akşamlardan bazıları, bojiler, tekerlek takımları, süspansiyon sistemleri, araç bağlantı elemanları ve tamponlardır. Bu tezde, demiryolu araçlarında özellikle tehlikeli madde taşıyan yük vagonlarında kullanılan, büyük kuvvetler etkidiğinde dış gövdesinde plastik deformasyona uğraması ile ortaya çıkan dinamik enerjiyi sönümleyen çarpışma tamponları incelenmiştir. Örnek bir çarpışma tamponu tasarımı mevcut çalışmalar ve standartlar doğrultusunda oluşturulmuştur. Oluşturulan çarpışma tamponu örneği üzerinde standartlarda yer alan statik ve dinamik testlerin bir simülasyonu uygulanmıştır. Tez beş ayrı kısımdan oluşmaktadır. Birinci kısımda, tezin amacı ifade edilmiştir. Ayrıca demiryolu araçları ve mekanik aksamları hakkında genel bilgiler bulunmaktadır. Bununla beraber, tamponlar ve çarpışma tamponları hakkında bilgiler mevcuttur. İkinci kısımda ise mevcut standartlar ve geçmişte yapılmış çalışmalar incelenmektedir. Standartlarda ifade edilen tampon uzunlukları ve tampon stroğu olarak ifade edilen hareket mesafesi değerleri, tampon destek plakası minimum ölçüleri ve mevcut çalışmalar yer almaktadır. Yapılan incelemeler ve standartlarda yer alan bilgiler neticesinde çarpışma tamponlarının tasarım kriterleri, kullanılan tampon malzemesi hakkında bilgiler ve statik ve dinamik testler ile ilgili bilgiler üçüncü kısımda yer almaktadır. Ayrıca bu kısımda, çarpışma tamponlarındaki toplam dinamik enerji hesabı yer almaktadır. Bunun yanı sıra, tasarımı yapılan örnek çarpışma tamponu sayısal modeli hakkında bilgiler verilmektedir. Sayısal model kurulumunda, statik kuvvetlerin uygulanması, dinamik analizin uygulanması ve kullanılan programlar hakkındaki bilgiler de yine bu kısımda yer almaktadır. Dördüncü kısımda ise mevcut bilgiler doğrultusunda tasarımı yapılan örnek çarpışma tamponuna uygulanan statik ve dinamik testlerin simülasyonu yer almaktadır. Simülasyonlar Ansys workbench programı içerisinde gerçekleştirilmektedir. Uygulanan statik testlerde tamponun kritik sabit bölgeleri üzerinde seçilen sekiz adet noktadaki gerimeler ve emniyet katsayısı değerleri bu kısımda incelenmektedir. Ayrıca yapılan statik analizler ile çarpışma tamponundaki gerilmeler ve deformasyonlar incelenmektedir. Dinamik analizde ise çarpışma tamponundaki plastik deformasyon neticesinde oluşan toplam dinamik enerji miktarı ve plastik deformasyonda sönümlenen dinamik enerji miktarı incelenmektedir. Bu hususta çarpışma tamponu vagona bağlandığı plaka üzerinden sabit tutulup, tampon destek plakasından yer değiştirme uygulanmıştır. Özellikle toplam enerji miktarının ve plastik deformasyon esnasında sönümlenen dinamik enerji miktarı standartlarda belirtilen değerde olması amaçlanmıştır. Plastik deformasyon sırasında sönümlenen enerji miktarı neticesinde çarpışma tamponunda kullanılan ince cidarlı tüplerin cidar kalınlıkları ve uzunlukları belirlenmiştir. Tüm bu çalışmalar doğrultusunda nihai bir temsili tasarım ölçüleri, tamponda kullanılan malzemeler gibi çarpışma tamponu tasarım unsurları beşinci kısımda, "Sonuç ve Öneriler" başlığı altında belirtilmiştir. Tasarımı yapılan çarpışma tamponunun teknik resimleri "Ek A" içerisinde; kullanılan malzemelerin teknik özellikleri ise tablo halinde "Ek B" içerisinde yer almaktadır.

Railway vehicles are the most significant parts of logistics from past to present. Because of this reason, safety of railway vehicles becomes the most important thing to protect humans, and freights in the railways for transportation. Especially, when railway vehicles are produced, the mechanical sections of these vehicles must provide rules of railway standards for the safety. These rules of standards provide to control the designed mechanical parts on railway vehicles when the static and dynamic tests in railway standards are applied to these mechanical sections of railway vehicles. There are a lot of mechanical parts on railway vehicles. Some of these mechanical sections are bogies, wheel units, suspension systems, coupling sets, and buffers. Besides, these parts are also varied in their types. At this thesis, crashworthy buffers which used on freight wagons to carry dangerous materials on railway vehicles, becoming to plastic deformation on the outer body when huge forces affects to body frames, and absorbing the dynamic energy along the plastıc deformation are researched. A sample of crashworthy buffer is designed in 3D design program as known Solidworks according to past and current studies and standards. On this designed crashworthy buffer sample, static and dynamic tests explained in standards are applied in a simulation program as known Ansys Workbench. This thesis consists of five sections. In the first section, the safety of railway vehicles is described, and the purpose of thesis is explained. Then, types of railway vehicles are classified as powered railcars, unpowered railcars, and railway track machines. Powered railcars, unpowered railcars, and railway track machines are varied, and all of these are described in the first section. Powered railcars are used to carry unpowered railcars. These are classified as locomotives and train sets in the first section. Locomotives are varied as steam locomotives, diesel locomotives, and electrical locomotives here. Furthermore, train sets are explained in this section. Unpowered railcars are used to transport passengers, and freights on the railroads via powered railcars because, these cannot move without any powered railcars. These are classified as passenger wagons, and freight wagons in the first section. Moreover, these classified railcars are explained in this section. Railway track machines are used to repair in railways or to build new railroads along the route. In addition to this, some of these machines are used for trouble shooting in railways. These are also classified, and explained in the first section. To sum up, all of railway vehicles are classified, and explained in section one. In addition, all of these vehicles are shown in figures in this section. On the other hand, interconnection components and buffers in railway vehicles are also described in the first section. Interconnection components are explained as couplers in railcars. In the second section, the present standards and scientific studies from past to present are investigated. There are a lot of standards about railway vehicles on the railways European National (EN) standards. However, EN 15551 is used to include more information for crashworthy buffers in this thesis. According to EN 15551 standard, the buffer minimum dimensions are defined in this section. Especially, buffer head minimum dimensions, buffer connection plate maximum dimensions, buffer total length, and buffer stroke are defined according to this standard. In addition, some studies are investigated in the second section at this thesis. Especially, past studies about crashworthy buffers are explained in this section. One of these studies name is "The study on New Crashworthy Buffer in Railway". In this study, buffer material is explained, and buffer model in simulation is described. In addition, the simulation specifications, material model, and used simulation program are expressed in the second section. Besides, this section consists of buffer simulation solutions. Another information in this section is study about metal tubes by S.R. REID. This study includes experiments and simulations of metal tubes. Here, buckling, inversion and splitting is investigated. Experimental results are expressed. Theoretical equation values of buckling on the metal tube is shown in this study. Then, the experimental results and theoretical equation values are compared here. In addition, the study about active-passive integration energy absorbers is shown in the second section of this thesis. Here, thin – walled tubes are investigated via some experimental data. The experiment is compression test. This test is applied to show the energy absorption of metal tubes when the crush is become on the active – passive integration energy absorber. The materials of the metal tube samples are Aluminum alloy AA 7075-T6 and AISI 1045 steel in this study. Here, material energy absorption results are shown in the table, and compared these metal and aluminum alloy tube samples. In the table, mean crushing forces, pick crushing forces and energy absorptions are shown. According to table, the performance and productivity of aluminum alloy tube samples are better than steel tube samples. In section three of this thesis, Design criteria of crashworthy buffers is explained. General conditions of crashworthy buffers, design criteria, basic calculations of energy absorption, and numerical model of crashworthy buffer sample is shown in this section. According to general conditions, third section of the thesis consists of static and dynamic conditions in the EN 15551 standard here. There are six static tests in static conditions of buffers in the standard. Values and applied locations of static forces are shown in this standard. In addition, buffer static characteristics are shown in the table here. The table includes static forces of buffers have separate stroke values. Also, energy absorption capacities of these buffers are shown in this section. On the other hand, dynamic conditions of crashworthy buffers are shown here. Dynamic conditions are explained in Annex J at EN 15551 standard. Also, RID 2019 shows the energy absorption conditions of crashworthy buffers in dynamic conditions.
Crashworthy buffer design
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2020
Keywords: demiryolu araçları; railway vehicles; tamponu tasarımı; buffer design